Prosedur Adopsi Anak Dalam Hukum - Suta Ramadan; Renita Agustiani; Erlangga Adnus (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Child adoption is a legal action that transfers a child from the sphere of power of parents, legal guardians or other people responsible for the care, education and raising of the child into the adoptive parents' family setting. This research is conducted with the aim of knowing how the concept of child adoption and how child protection efforts in Indonesia are associated with the practice of child adoption. This study used a normative juridical approach in order to accomplish its goals. Descriptive analytical research specifications are used. The protection of children regulated in the Law of the Republic of Indonesia Number 35 of 2014 concerning Amendments to Law of the Republic of Indonesia Number 23 of 2002 concerning Child Protection is still not running effectively due to various forms of abuse directed to the child's home environment, including child abuse practices where the child fails to follow the rules or procedures, there are potential consequences that can cause the child to become less normal.